REGIONAL RADIO AS A POLITICAL COMMUNICATOR: THE ROLE OF SWARA TANGERANG GEMILANG RADIO IN PROMOTING THE POLITICAL PARTICIPATION - Muhammad Daffa Virigiawan; Iding Rosyidin (Jurnal Ranah Komunikasi, 2026)
This study examines Swara Tangerang Gemilang Radio, a regional radio station in Tangerang Regency, and its role as a political communicator in promoting political participation among the people of Tangerang Regency in 2019. As is well known, 2019 has been a political year because it coincides with Indonesia's general elections. In this context, Swara Tangerang Gemilang Radio has a mandate to engage in political communication based on Tangerang District Regent Regulation No. 13 of 2016. This research was conducted using a descriptive qualitative method, using interviews and documentation data collection techniques. Moreover, the data analysis technique used in this study is the Miles and Huberman model. This study is based on the theory of political participation and incorporates the concepts of political communication and radio broadcasting. The study's results show that Radio Swara Tangerang Gemilang, as a political communicator, plays a role in shaping political messages and disseminating political information to the public. Control of messages carried out by Radio Swara Tangerang Gemilang is in the planning and implementation stages. Control over the message, then produces output in the form of messages conveyed to the people of Tangerang Regency to participate in politics, such as public discussions on messages from Radio Swara Tangerang Gemilang.